SPORTS NUTRITION FOR BASKETBALL PLAYERS DURING THE PREPARATION PERIOD - Василенко, Вадим (SWorldJournal, 2025)
studying the rational nutrition of basketball players is a current problem, since its correct solution contributes to maintaining health and vital functions of the body during training and competitions